Informação & Informação Vol. 19, n. 1 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Informação & Informação Vol. 19, n. 1 (2014) Link de acesso ao númerohttp://www.uel.br/revistas/uel/index.php/informacao/issue/view/919